The Viennese Ballroom in the Age of Beethoven - Buurman, Erica (Cambridge New York Cambridge University Press, 2022)
"Viennese musical life in the decades around 1800 was shaped by significant social, economic and political changes which transformed the way music was produced and consumed. By far the most celebrated manifestation of these changes is the career trajectory of Ludwig van Beethoven. From his initial employment as a salaried member of a court orchestra, Beethoven moved to Vienna where he learned to navigate new forms of aristocratic patronage, concert-giving and the burgeoning commercial music publishing market in order to forge a career as an independent artist. Much has been written about the developments in culture and society that had a direct impact on Beethoven's compositional activities, particularly in the areas of aristocratic patronage and developments in concert life"--
The Public Ball in Viennese Musical Life, 1770-1830 -- Early Waltz Dances of the Viennese Ballroom : Transmission and Transformation in Eighteenth-Century Music and Dance -- The Minuet : Performing Aristocracy in the Viennese Ballroom -- The Contredanse : Participation and Spectatorship in the Public Ballroom -- Dance Arrangements from the Viennese stage -- Battle Waltzes : Programmatic Music in the Ballroom -- 'The Congress Dances' : The Viennese Public Ball and Court-Sponsored Festivities at the Congress of Vienna.
Includes bibliographical references and index.
Keywords: Beethoven, Ludwig van -- 1770-1827; Dance; Music history; Vienna (Austria)